Development of Moodle-Based E-Learning at LKP TIKOM - Mochammad Agri Triansyah; Mochamad Guntur; Diah Afrianti Rahayu (Ilmu Inovasi Nusantara, 2022)
This research is a research development. It said development research because this study concluded a product that is research using the Research and Development method. This research is directed to develop E-learning media based on a Website using Moodle platform with additional Video Conference features. This research uses the Waterfall method. This Waterfall method approaches systematically and sequentially in building software. Product trials are carried out in two ways, theoretically and empirically. Theoretically, an attempt was conducted on the feasibility test for using E-learning with the assessment of media experts and assessors/students while empirically testing the product using the black box. That the development of website-based E-learning uses the Moodle platform with additional video conference features (1) Attracting course and training participants and (2) Assisting the Instructor's task in increasing competency at LKP TIKOM